2021
DOI: 10.1093/gerona/glab117
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Polygenic Risk for Alzheimer’s Disease Predict Conversion to Alzheimer’s Disease

Abstract: Body mass index (BMI) is a risk factor for Alzheimer’s disease (AD) although the relationship is complex. Obesity in midlife is associated with increased risk for AD, whereas evidence supports both higher and lower BMI increasing risk for AD in late life. This study examined the influence of individual differences in genetic risk for AD to further clarify the relationship between late-life BMI and conversion to AD. Participants included 52 individuals diagnosed as having mild cognitive impairment (MCI) at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Sex hormone and inflammation seemed to be involved. For example, among people genetically susceptible to AD, a stronger risk of AD was observed in men with lower BMI compared with women, possibly due to the identification of testosterone as a risk factor for AD in the preclinical phase and its association with adipogenesis inhibition in men 22 . In addition, findings point to that obesity in women leads to a greater increase in inflammatory responses than in men, and there is a greater association between inflammation and AD risk in women 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormone and inflammation seemed to be involved. For example, among people genetically susceptible to AD, a stronger risk of AD was observed in men with lower BMI compared with women, possibly due to the identification of testosterone as a risk factor for AD in the preclinical phase and its association with adipogenesis inhibition in men 22 . In addition, findings point to that obesity in women leads to a greater increase in inflammatory responses than in men, and there is a greater association between inflammation and AD risk in women 23 .…”
Section: Discussionmentioning
confidence: 99%
“…For further confirmation, consider again the information in Table 1. In the first section of the table, empirical values of the mean, standard deviation, skewness, and kurtosis of ANSUR heights H and weights W are compared with corresponding values predicted by lognormal expressions (7) to (10), based on the parameters in the second section of the table, derived from the variates of lnH and lnW. Agreement of experiment and theory is seen to be within 1 standard error (se) in most cases.…”
Section: Marginal Statistics Of Ansur Height and Weight Datamentioning
confidence: 99%
“…Although more refined studies have revealed that anthropometric data can show deviations from normality, attempts to find relationships between human height and weight remained uncertain, controversial and based on approximate or indirect methods such as data fitting [5], mechanical modeling [6], and gene identification [7]. Height and weight are of particular importance since they directly relate to the body mass index (BMI) [8], which is a measure of obesity and a risk factor for metabolic disease [9] and Alzheimer's Disease [10]. A previous paper by Silverman and Lipscombe [11], to be referred to as Part I, determined the mathematically exact statistical distribution of BMI.…”
Section: Introductionmentioning
confidence: 99%
“…People suffering from MCI have a high rate of progression to dementia over a relatively short period, but not everyone will develop AD [ 3 ]. Within a 3-year follow-up period, about 35% of patients with MCI status progress to AD or dementia [ 4 ]. A yearly conversion rate equals 5% –10% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%